2014
DOI: 10.5607/en.2014.23.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Aucubin Promotes Neurite Outgrowth in Neural Stem Cells and Axonal Regeneration in Sciatic Nerves

Abstract: Aucubin is an iridoid glycoside with a wide range of biological activities, including anti-inflammatory, anti-microbial, anti-algesic as well as anti-tumor activities. Recently, it has been shown that aucubin prevents neuronal death in the hippocampal CA1 region in rats with diabetic encephalopathy. In addition, it has protective effects on H2O2-induced apoptosis in PC12 cells. We have shown here that aucubin promotes neuronal differentiation and neurite outgrowth in neural stem cells cultured primarily from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…plants Plantago lanceolata L. and Veronica officinalis L. (Plantaginaceae). Several pharmacological benefits have been reported for aucubin, such as hepatoprotective [7], anti-inflammatory [8], anti-oxidant [9,10], anti-osteoporosis [11], and neurotrophic effects [12,13]. Lv et al [14] reported that aucubin reduced the protein expression of α-SMA, collagen I, collagen III, and MMP-2, suppressed the generation of reactive oxygen species, and down-regulated the nicotinamide adenine dinucleotide phosphate-oxidase-4 mRNA expression in LX-2 cells.…”
Section: Aucubin Protects Against Tgfβ1-induced Cardiac Fibroblasts Amentioning
confidence: 99%
“…plants Plantago lanceolata L. and Veronica officinalis L. (Plantaginaceae). Several pharmacological benefits have been reported for aucubin, such as hepatoprotective [7], anti-inflammatory [8], anti-oxidant [9,10], anti-osteoporosis [11], and neurotrophic effects [12,13]. Lv et al [14] reported that aucubin reduced the protein expression of α-SMA, collagen I, collagen III, and MMP-2, suppressed the generation of reactive oxygen species, and down-regulated the nicotinamide adenine dinucleotide phosphate-oxidase-4 mRNA expression in LX-2 cells.…”
Section: Aucubin Protects Against Tgfβ1-induced Cardiac Fibroblasts Amentioning
confidence: 99%
“…Aucubin, a compound isolated from traditional Korean medicinal herbs, such as Aucuba japonica, Eucommia ulmoides, Plantago asiatica and Melitaea cinxia, was originally identified as an antioxidant (Kim et al, 2014). Aucubin has since been shown to have multiple pharmacological effects, including BP reduction and liver protection as well as antiinflammatory (Kim et al, 2014) and anti-apoptotic effects and regulation of autophagy . The profound effects of aucubin on oxidative stress, inflammation and apoptosis suggests a potential application for aucubin in cardiovascular disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…Aucubin has been shown to protect neurons from cell death by changing antioxidative ability and the expression of Bcl-2 and Bax in the rat model of diabetic encephalopathy [ 7 20 ]. Thus, aucubin seems to protect neurons by enhancing neuronal survival and reducing apoptotic cells, whereas we recently found that aucubin facilitates the neurite outgrowth of hippocampal NPCs primarily cultured from rat embryos (E16) and axonal elongation in the injured peripheral nervous system [ 10 ]. There are also reports that natural lignans and iridoid compounds including aucubin lengthen the neurites of PC12h cells, a cultured cell line of paraneuron [ 8 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the nervous system, aucubin has been shown to have neuroprotective effects by enhancing neuronal survival and reducing apoptotic cells [ 6 7 ]. There have been, however, several reports suggesting that aucubin might have effects on facilitating neuronal differentiation in addition to neuronal protection and survival, including our previous studies [ 8 9 10 ]. Despite the known effects of aucubin on various biological activities, little is known about its effects on neuronal differentiation.…”
Section: Introductionmentioning
confidence: 85%